Is community water management the community’s choice? Implications for water and development policy in Africa - Hope, R (IWA Publishing, 2014)
The global drive for universal drinking water security has faltered in rural Africa. Community management of handpumps, which provide water to over 200 million rural people, is the prevailing but increasingly embattled policy choice. A choice experiment is designed to test alternative maintenance models across competing attributes of maintenance provider, maintenance level, payment mode, and payment level. A sample of 3,540 observations is modeled from 118 handpump users in rural Kenya. Results identify community management of maintenance services as the least preferred option with water user payments contingent on an order of magnitude improvement in handpump repair times. Social choice heterogeneity varies by socio-economic status and water use behaviors indicating uneven adoption profiles within communities compounded by no acceptable payment mode. Policy responses to community choices need to address these institutional challenges through new monitoring platforms and acceptable payment systems.